2003
DOI: 10.1016/s0014-5793(03)00098-x
|View full text |Cite
|
Sign up to set email alerts
|

Arfaptin 1 inhibits ADP‐ribosylation factor‐dependent matrix metalloproteinase‐9 secretion induced by phorbol ester in HT 1080 fibrosarcoma cells

Abstract: Matrix metalloproteinase-9 (MMP-9) is a collagenolytic enzyme secreted by cancer cells and involved in invasiveness and metastasis. Its secretion from human ¢brosarcoma HT 1080 cells is markedly enhanced by phorbol 12-myristate 13-acetate (PMA) and abolished by brefeldin A, an inhibitor of ADP-ribosylation factor (ARF) activation. These results support a role for ARF in PMA-stimulated MMP-9 secretion. Overexpression of arfaptin 1, a 39 kDa ARF-binding protein that inhibits in vitro activation of cholera toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…We hypothesize that these shed vesicles may play a role in pericellular proteolytic activity under physiological and pathological conditions. Our data show that BFA treatment on reactive astrocytes inhibits MMP-2 and MMP-9 secretion with a concomitant intracellular increase, indicating a Golgidependant secretory pathway for these proteins, as described in N2a, endothelioma, and fibrosarcoma cells (Ho et al, 2003;Sbai et al, 2008;Taraboletti et al, 2000). Our findings are in line with previous reports demonstrating secretion of metalloproteinases as a component of intact membrane vesicles rather than as soluble enzymes, as shown in cultured malignant mouse melanoma (Zucker et al, 1987).…”
Section: Vesicular Secretion Of Mmp-2 Mmp-9 and Their Endogenous Insupporting
confidence: 92%
“…We hypothesize that these shed vesicles may play a role in pericellular proteolytic activity under physiological and pathological conditions. Our data show that BFA treatment on reactive astrocytes inhibits MMP-2 and MMP-9 secretion with a concomitant intracellular increase, indicating a Golgidependant secretory pathway for these proteins, as described in N2a, endothelioma, and fibrosarcoma cells (Ho et al, 2003;Sbai et al, 2008;Taraboletti et al, 2000). Our findings are in line with previous reports demonstrating secretion of metalloproteinases as a component of intact membrane vesicles rather than as soluble enzymes, as shown in cultured malignant mouse melanoma (Zucker et al, 1987).…”
Section: Vesicular Secretion Of Mmp-2 Mmp-9 and Their Endogenous Insupporting
confidence: 92%
“…49,50 However, in this study, both brefeldin A and monensin failed to block the rapid MMP-9 release induced by ATP or PMA over 30 minutes, suggesting that rapid MMP-9 release may occur via granule secretion, similar to membrane type 1 matrix metalloproteinase (MT1-MMP), which rapidly traffics to the plasma membrane via an unconventional brefeldin A-resistant pathway. 51 In support of this concept, it has been shown that B lymphocytes contain MMP-9 in a granular distribution.…”
contrasting
confidence: 55%
“…We tested if DN‐ARF6 and DN‐Rac1 can inhibit PMA‐induced ruffling. We also examined if DN‐ARF1 also inhibits the ruffling because of evidence that ARF1 is involved in some aspects of PMA signaling (Ho et al, 2003) and PLD activation (Shome et al, 1998). RhoA and Cdc42 were used as controls.…”
Section: Resultsmentioning
confidence: 99%